PELATIHAN PERHITUNGAN PENYUSUTAN ASET TETAP METODE GARIS LURUS VS MACRS DAN IMPLIKASI PADA LABA SEBELUM PAJAK - Agusman Agusman; Risa Wahyuni EDT; Winona Kumara Dewi; Erniwati Erniwati; Fathiah Fathiah; Alhazar Rinaldi (Jurnal Pengabdian Masyarakat, 2024)
Accounting students essentially learn the process of preparing financial statements for companies. Among the various accounts in financial statements, one is the fixed asset account. When calculating fixed assets, depreciation expenses must be considered, as asset values can decrease over time. This training aims to enhance students' understanding and compare the straight-line method applied in Indonesia with the MACRS method used in the United States. Calculating depreciation using MACRS is not taught in accounting courses. However, in line with our objectives, we are conducting this training to calculate depreciation expenses and compare the two methods to analyze their implications for gross profit. The methods employed in this activity are lectures and discussions. It is expected that through this program, students will broaden their knowledge and gain insight into how depreciation expense calculations differ between countries. The financial statements to be used in this activity are from PT Unilever Tbk.